Management of type 2 diabetes mellitus: Is it in accordance with the guidelines? - Chan, G.C.; Ghazali, O.; Khoo, Ee Ming (Malaysian Medical Association, 2005)
A cross-sectional study was conducted among 517 patients with diabetes mellitus at all health centres in Melaka Tengah District to examine whether these patients and their associated cardiovascular risk factors were managed according to current guidelines. All patients had Type 2 diabetes mellitus with mean age of 57.9110.5 years and the mean duration of diabetes was 7.2 Â± 6.0 years. The gh/caemic control was poor with 53.6 of the patients having HbA1c above 8 (mean-8.5) and 24 of them had microalbuminuria. Among these patients with poor glycaemic control, about 47.6 of them were on monotherapy. Three hundred and fifty (67.7) patients had hypertension but only 11 (3.1) achieved target blood pressure of less than 130/80 mmHg. Only 18.3 of the diabetics with hypertension were prescribed angiotensin converting enzyme inhibitors and 0.3 with angtotensin receptor blockers. Nearly two-third of them had low-density lipoprotein cholesterol greater than 2.6 mmol/l (mean-3.4 mmol/l) but only 6.8 were prescribed lipid-towering agents. Aspirin was prescribed to 8.2 of diabetics aged above 40 years. Sixteen percent of the patients smoked, 53 did not do any exercise, and the mean BMI was 26.8 kg/m2. The management of diabetes mellitus and its associated cardiovascular risk factors was sub-optimal on the basis of current clinical guidelines. A greater effort in educating doctors in the health centres about these management and adherence to the guidelines is important in reducing patients' risk of cardiovascular disease and its associated morbidity and mortality.